Mycobacterium abscessus and β-Lactams: Emerging Insights and Potential Opportunities - Story-Roller, Elizabeth; Maggioncalda, Emily C.; Cohen, Keira A.; Lamichhane, Gyanu (Frontiers in Microbiology, 2018)
β-lactams, the most widely used class of antibiotics, are well-tolerated, and their molecular mechanisms of action against many bacteria are well-documented. Mycobacterium abscessus (Mab) is a virulent and highly drug-resistant rapid-growing nontuberculous mycobacteria (NTM), however, only in recent years have we begun to gain insight into the unique relationship between β-lactams and their targets in Mab. In this mini-review, we summarize recent findings that have begun to unravel the molecular basis for overall efficacy of β-lactams against Mab and discuss emerging evidence that indicates that we have yet to harness the full potential of this antibiotic class to treat Mab infections.